2020
DOI: 10.1002/lio2.469
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D in head and neck cancer

Abstract: Objective: Head and neck squamous cell carcinoma (HNSCC) describes a set of malignancies of the head and neck that continue to inflict considerable morbidity and mortality. Because HNSCC often presents at an advanced stage, patients frequently undergo intensive multi-modal therapy with an intent to cure. Vitamin D is a precursor to the biologically active hormone calcitriol which governs bone and calcium physiology that is obtained from diet and UV-B exposure. Vitamin D is known to have pleiotropic effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…In current study, there were more men than women (5,21), who were reported to have two-fold greater risk of developing HNC than women due to tobacco consumption, alcohol consumption, oropharyngeal cavity hygiene, and human papillomavirus (HR-HPV) infection (3,5,9). Most nasopharyngeal keratinizing squamous cell carcinoma was found in current study, while in other studies, different types of primary tumors and stages of cancer were focused.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In current study, there were more men than women (5,21), who were reported to have two-fold greater risk of developing HNC than women due to tobacco consumption, alcohol consumption, oropharyngeal cavity hygiene, and human papillomavirus (HR-HPV) infection (3,5,9). Most nasopharyngeal keratinizing squamous cell carcinoma was found in current study, while in other studies, different types of primary tumors and stages of cancer were focused.…”
Section: Discussionmentioning
confidence: 64%
“…(7) Vitamin D could increase T cell activation by increasing the expression of CD4, CD8, and CD69. (8,9) Vitamin D is mainly activated by the binding of 1alpha,25 Dihydroxyvitamin D (1,25(OH)D) (active form) or 25(OH) D (less active form) to the Vitamin D Receptor (VDR), including nuclear receptor members of regulatory genes, which have anti-inflammatory and anti-proliferation activities. (10)(11)(12) Routine examinations of vitamin D levels are often carried out to check the serumal 25(OH)D level, although the active form of vitamin D is 1,25(OH)D. This active form is produced predominantly by the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies indicate potential associations between vitamin D and HNC, and supplementation of micronutrients has been proposed to prevent several cancers. (61)(62)(63)(64)(65) HNSCC…”
Section: Micronutrient (Vitamins and Minerals Supplementation)mentioning
confidence: 99%
“…Pu et al performed a meta-analysis evaluating Vit D3 exposure and HNC incidence and mortality, and the possible effects of VDR polymorphisms [ 164 ]. They reported an inverse association between the two aforementioned parameters and dietary or supplemental Vit D3 intake, which improved prognosis and quality of life [ 165 ].…”
Section: Vitamin D and Cancermentioning
confidence: 99%